STRESS AND HEALTH - Đorđe Mačvanin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
All people have reaction to stress, but owing to their specific business, managers are exposed to some of, so called, manage, diseases. The essential problems of these diseases are those related to circulation of blood, especially with arteries, which can cause a lot of organic problems. From the aspect of psychology, there is a faster work of hart and regardless the stressor being positive or negative. Total condition is under ifluence of adrenalin and cortisone, which help organism in suppy of energy. The present problem is that stress have psycho-mental origin, but in the past it was belived to be of physical character, so that energy instead of being used for physical activity, it remains stored in especially in arteries, because of insufficient consumption through physical activity, and failure to understand techniques of over coming stress.